Effect of Obesity and Being Overweight on Disability and Pain After Lumbar Fusion: An Analysis of 805 Patients. Issue 9 (May 2016) - Sorimachi, Yasunori; Neva, Marko H.; Vihtonen, Kimmo; Kyrölä, Kati; Iizuka, Haku; Takagishi, Kenji; Häkkinen, Arja
Abstract : Study Design: Prospective follow-up study. Objective: To investigate the influence of obesity and being overweight on disability and pain of patients undergoing lumbar spinal fusion. Summary of Background Data: Although spinal fusion surgery has been shown to relieve symptoms in several spinal disorders, the influence of obesity on the results remains controversial. Methods: Since January 1, 2008, all patients undergoing lumbar fusion in two hospitals have been invited to participate in a prospective follow-up database. At the end of 2014, the preoperative and 1-year follow-up data of 805 patients were available. Disability was evaluated using the Oswestry Disability Index and back and leg pain by the visual analogue scale. In addition, the working status, smoking, physical activity, duration of symptoms, and indication for surgery were captured. According to the World Health Organization classification of preoperative body mass index, patients were divided into three groups: normal weight (<25.0 kg/m 2 ), overweight (25.0–29.9 kg/m 2 ), and obese (≥30.0 kg/m 2 ). Results: Of the 805 patients, 204 (25.3%) were normal weight, 365 (45.3%) were overweight, and 236 (29.3%) were obese. The patients in the obese group exercised significantly less per week ( P  < 0.001). Preoperatively, the body mass index groups did not differ with regard to disability and pain. At the 1-year follow-up, the change in the Oswestry Disability Index was −25 in normal, −24 in overweight, and −23 in obese patients ( P  = 0.013), and disability was severe in 14.7% of the normal group, 17.0% of the overweight group, and 24.2% of the obese group ( P  = 0.0052). Back and leg pain improved more in the normal weight group compared with the overweight or obese groups ( P  < 0.05). Conclusion: Although lumbar spine fusion is also effective in obese patients, the present large follow-up study demonstrates that their outcome results are slightly poorer than patients with normal weight at 1 year after surgery. Level of Evidence: 3